ChemInform Abstract: Stereoselective Synthesis of Mexiletine and Structural Analogues with Chiral tert‐Butanesulfinamide. Issue 44 (15th October 2015) - Ryan, Daniel A.; Okolotowicz, Karl J.; Mercola, Mark; Cashman, John R.
Abstract The approach relies on a two‐step condensation‐reduction procedure, and the stereochemical outcome is reversed by the appropriate reducing agent.